Initial Reports of the Deep Sea Drilling Project 1980
DOI: 10.2973/dsdp.proc.515253.152.1980
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Geochemistry of Alteration Products in Holes 417A and 417D Basement Samples (Deep Sea Drilling Project Leg 51)

Abstract: The striking difference between the basalts of Hole 417A (strongly altered) and those of Hole 417D (slightly altered) is one of the main discoveries of Legs 51-52. After a macroscopic description of the two basaltic sections, the authors describe the mineralogy of alteration in the two holes. In Hole 417D, the pillow margins exhibit a nice concentric zoning, with a hyaloclastic zone, a glassy zone, a variolitic zone, a spherolitic zone, and the pillow core. Fresh black and brilliant glass is abundant; it is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
2
17
0
1
Order By: Relevance
“…Earlier studies of submarine basalt alteration (e.g., Ijima and Harada, 1969;Bass, 1976) have concluded that di-and trioctahedral smectites are typical of low temperature alteration, or halmyrolysis (Melson and Thompson, 1973;Andrews et al, 1977;Seyfried et al, 1976;Robinson et al, 1977;Juteau et al, 1980) and that mixed-layer chlorite-smectites, associated with zeolites such as analcite, are index minerals for hydrothermal alteration (Humphris and Thompson, 1978). The samples studied here show trioctahedral smectites replaced by mixed-layer minerals.…”
Section: Discussionmentioning
confidence: 71%
“…Earlier studies of submarine basalt alteration (e.g., Ijima and Harada, 1969;Bass, 1976) have concluded that di-and trioctahedral smectites are typical of low temperature alteration, or halmyrolysis (Melson and Thompson, 1973;Andrews et al, 1977;Seyfried et al, 1976;Robinson et al, 1977;Juteau et al, 1980) and that mixed-layer chlorite-smectites, associated with zeolites such as analcite, are index minerals for hydrothermal alteration (Humphris and Thompson, 1978). The samples studied here show trioctahedral smectites replaced by mixed-layer minerals.…”
Section: Discussionmentioning
confidence: 71%
“…A!teration products include, in decreasing order of volume, clay minerals, carbonates, K-feldspars, zeolites, silica, iron oxyhydroxide, opaque minerals, and chlorite (Pritchard 1980;Humphris et al, 1980;Rusinov, 1980, Scheidegger andStakes, 1980;Rusinov et al, 1980a;Juteau et al, 1980, Mevel, 1980Gitlin, 1985). 59 was altered to K-rich celadonite and/or nontronite by early low-temperature oxidative alteration.…”
mentioning
confidence: 99%
“…Chemical budget implications of the alteration of basaltic glass to palagonite are discussed by Juteau et al (1980) andHart (1983). 180 is enriched in altered basalt increasing 5180 (Muehlenbachs, 1980;Javoy and Fouillac, 1980).…”
mentioning
confidence: 99%
“…Thompson (1983) recalculated elemental fluxes for 418A (his Table 47.14) and 417A (his Table 47.16). Chemical budget implications of the alteration of basaltic glass to palagonite are discussed by Juteau et al (1980) andHart (1983). 18Q is enriched in altered basalt increasing (518Q (Muehlenbachs, 1980;Javoy and Fouillac, 1980).…”
mentioning
confidence: 99%
“…Alteration products include, in decreasing order of volume, clay minerals, carbonates, K-feldspars, zeolites, silica, iron oxyhydroxide, opaque minerals, and chlorite (Pritchard 1980;Humphris et al , 1980;Rusinov, 1980, Scheidegger andStakes, 1980;Rusinov et al ., 1980a;Juteau et al, 1980, Mevel, 1980Gitlin, 1985). ..…”
mentioning
confidence: 99%